2020
DOI: 10.9734/cjast/2020/v39i3231008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Density and Nitrogen Management for Realizing Higher Cane Yield under Bud Chip Method of Planting in Sugarcane (Saccharum officinarum)

Abstract: A field experiment was conducted at Regional Sugarcane and Rice Research Station, Rudrur, during 2018-19 to study the effect of plant density and nitrogen management for realizing higher cane yield under bud chip method of planting in sugarcane (Saccharum officinerum). The treatments were plant geometry and nitrogen doses with three and four splits of application in split plot design. The recommended dose of nitrogen was 250 kg N ha-1. Among the geometry, 150 x 60 cm spacing recorded significantly higher cane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In tropical condition, planting of sugarcane bud chip settling at spacing of 150 cm  45 cm along with the application of composted coir pith @ 5 or 10 t/ha and 75% recommended level of irrigation performed better than planting at a spacing of 150 cm  60 cm (Dhanapal et al, 2019). On the contrary, Swapna et al (2020) reported that among the different planting geometry of bud chip method, 150 cm  60 cm was found to be most suitable in terms of cane length, tiller numbers internode length as well as cane yield (162 tha -1 ) as compared to other planting geometry.…”
Section: Cane Yield Of Sugarcane Influenced By Different Planting Geo...mentioning
confidence: 94%
See 1 more Smart Citation
“…In tropical condition, planting of sugarcane bud chip settling at spacing of 150 cm  45 cm along with the application of composted coir pith @ 5 or 10 t/ha and 75% recommended level of irrigation performed better than planting at a spacing of 150 cm  60 cm (Dhanapal et al, 2019). On the contrary, Swapna et al (2020) reported that among the different planting geometry of bud chip method, 150 cm  60 cm was found to be most suitable in terms of cane length, tiller numbers internode length as well as cane yield (162 tha -1 ) as compared to other planting geometry.…”
Section: Cane Yield Of Sugarcane Influenced By Different Planting Geo...mentioning
confidence: 94%
“…The planting of bud chip seedlings along with 75 per cent recommended dose of NPK + Azophos+ insitu incorporation of sunnhemp + foliar spraying of sugarcane booster (S3N4) recorded higher establishment percentage (87.89), plant height (246.35 cm), tiller population (123.25, 000 ha -1 ), dry matter production (92.21 t ha -1 ) , single cane weight (1.95 kg), seed cane yield (105.99t ha -1 ) as compared to other planting materials and nutrient management (Sugeerthi et al, 2018). The performance of sugarcane in bud chip technology also depends upon the fertilizer dose and method of application like the conventional method of planting (Swapna et al, 2020). They reported that the yield attributing characters as well as yield increased with the application of 150% recommendation of dose of fertilizers (RDF) than the 100% RDF.…”
Section: Performance Of Sugarcane Bud Chip Seedling Under Different N...mentioning
confidence: 99%